Potential Development of Volunteer Monks to Heal Patient’s Minds by Dharmas - et. al., Supitcha Pornpitchanarong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article discusses a research study about the potential development of Volunteer Monks group to heal patient’s mind by harmonizing Buddhist principles and consistent psychological principles. From the analysis of the current situation by interviewing the president of Volunteer Monks group about the development strategy of Volunteer Monks in the healing of patient’s minds in hospitals found that the selection of methods for developing strengths and the enhancement of the capacity of volunteer monks in order to weaknesses and obstacles such as time constraints and the number of volunteer monks. With the integration of Buddhist knowledge and psychology to heal patient’s mind causes the healing of the patient to be more effective along with enhancing confidence of volunteer monks in the long-term as well..